Synchronous in-field application of life-detection techniques in planetary analog missions. (February 2015) - Amador, Elena S.; Cable, Morgan L.; Chaudry, Nosheen; Cullen, Thomas; Gentry, Diana; Jacobsen, Malene B.; Murukesan, Gayathri; Schwieterman, Edward W.; Stevens, Adam H.; Stockton, Amanda; Yin, Chang; Cullen, David C.; et al.
Abstract: Field expeditions that simulate the operations of robotic planetary exploration missions at analog sites on Earth can help establish best practices and are therefore a positive contribution to the planetary exploration community. There are many sites in Iceland that possess heritage as planetary exploration analog locations and whose environmental extremes make them suitable for simulating scientific sampling and robotic operations. We conducted a planetary exploration analog mission at two recent lava fields in Iceland, Fimmvörðuháls (2010) and Eldfell (1973), using a specially developed field laboratory. We tested the utility of in-field site sampling down selection and tiered analysis operational capabilities with three life detection and characterization techniques: fluorescence microscopy (FM), adenine-triphosphate (ATP) bioluminescence assay, and quantitative polymerase chain reaction (qPCR) assay. The study made use of multiple cycles of sample collection at multiple distance scales and field laboratory analysis using the synchronous life-detection techniques to heuristically develop the continuing sampling and analysis strategy during the expedition. Here we report the operational lessons learned and provide brief summaries of scientific data. The full scientific data report will follow separately. We found that rapid in-field analysis to determine subsequent sampling decisions is operationally feasible, and that the chosen life detection and characterization techniques are suitable for a terrestrial life-detection field mission. In-field analysis enables the rapid obtainment of scientific data and thus facilitates the collection of the most scientifically relevant samples within a single field expedition, without the need for sample relocation to external laboratories. The operational lessons learned in this study could be applied to future terrestrial field expeditions employing other analytical techniques and to future robotic planetary exploration missions. Highlights: Fieldwork undertaken in Icelandic lava fields is described. Decision-making strategies and applications to space missions are investigated. Several analytical techniques were used to simulate a life detection mission. The approach used is suitable for heuristic development of sampling strategies.